The Digitization of White Women's Tears - Niki Messmore (Arizona State University, 2021)
Social media is a digital mirror of society. Across disciplines, scholars have written of social justice as it exists and as it should be within higher education and beyond. Looking to social media spaces where higher education practitioners and scholars interact with one another, we can see how scholars who discuss social justice initiatives can themselves perpetuate systems of oppression. Utilizing Mamta Motwani Accapadi's (2007) article "When White Women Cry: How White Women's Tears Oppress Women of Color" as a foundation, I reflect through poetry on how white women in positions of power within higher education engage in harmful behavior in digital spaces. Finally, I provide recommendations on how fellow white women can disrupt these acts of oppression.